SISTEM KONTROL PADA ROBOT PEMINDAH BARANG TIPE CARTESIAN CORDINAT MENGGUNAKAN ARDUINO UNO R3 - Darmawan, Dwiki; Sutisna, Setya Permana; Sutoyo, Edi (Universitas Ibn Khaldun Bogor, 2018)
Robots are an option to help human jobs address issues of precision, security and flexibility. The robotarm becomes one of the robot types that can help human work. The robot arm controller research isto control the stepper motor's motion according to the command. Desai this cartesian coordinaterobot is 2 axis that is X and Y axis. Control of this robot arm using Visual Basic 6.0 programming forcontrolled robot from PC to arduino Uno R3. Motor driver used is IC A4988, stepper motor movementgot input from PC with software visual basic 6.0. to move the stepper motor. Data sent from PC toArduino Uno R3 is a command from Visial Basic 6.0 with serial communication. The microcomputerreads the serial data input and sends a step value data to the stepper motor driver to move the robotarm. The end result of the robot arm controller research that has been achieved is the robot arm canbe controlled with the command to enter the distance that will be run by stepper motor as themethod of pemograman which is controlled through serial communication with Visual Basic 6.0. Thetest results show an average error 22.26531 for the left and 52.61111 for the right direction on X axiswhile for Y axis -5,36957 for the downward direction and 0.117647 for the upper direction